P200 7α-Hydroxy-4-cholesten-3-one for diagnosis and management of bile acid malabsorption in IBD patients: 2-year clinical experience. (25th January 2019) - Friedli, B; Prost, J-C; Brunner, F; Misselwitz, B; Wiest, R; Macpherson, A; Juillerat, P
Abstract: Background: 7α-Hydroxy-4-cholesten-3-one (7αC4) is a reliable method to diagnose bile acid malabsorption (BAM) which occurs frequently in inflammatory bowel diseases (IBD) patients. Since 7HCO is an intermediate metabolite in the bile acid synthesis, increased levels reflect bile acid production, which is the case in BAM. Methods: We analysed the results of a simple and rapid (6 min), ultra-high-performance liquid chromatography–tandem mass spectrometry method 1 to measure 7αC4 on patients prospectively encountered at Bern University Hospital gastroenterology outpatient clinic with symptoms of BAM. The serum test result was correlated with clinical data such as type of disease (IBD, IBS, SIBO), symptoms (diarrhoea) and postsurgical state (eg, Ileo- caecal resection) and clinical response to bile acid sequestrants (the decision to treat with cholestyramine was at the discretion of the treating physicians). Results: Two hundred forty-five patients were tested, among them 62 (25%) with IBD (50 Crohn's disease (CD) and 12 ulcerative colitis). The 7αC4 values of the subgroups showed a strong clinical validity with the highest values, as expected, in IBD (vs. controls, p < 0.0001), CD patients (vs. IBD, p = 0.002), after IC resection (compared with non-resected CD, p < 0.0001) and with response to cholestyramine ( p = 0.03) with or without diarrhoea ( p = NS). A value of 7αC4 in the serum higher than 48 ng/ml had a positive predictive value of more than 80% for treatment success of the diarrhoea with bile acid sequestrants in all patients (sensitivity 74% and specificity 82%), with an AUC of 0.8514 in the ROC curve for this threshold. For the 50 CD patients with or without intestinal resection this threshold goes up to 234 ng/ml (sensitivity 67%, specificity 83%; AUC 0.7857). 7αC4 levels according to response in 50 CD patients. ROC curve for 7αC4 50 CD patients. Conclusions: 7αC4 levels in the serum correlate strongly with the clinical likelihood of bile acid malabsorption in IBD patients. A threshold of 234 ng/ml could be identified to predict response to cholestyramine treatment. Reference 1. Prost J-C, Brunner F, Bovet C, et al. A UHPLC-MS/MS method for the quantification of 7α-hydroxy-4-cholesten-3-one to assist in diagnosis of bile acid malabsorption. Clin Mass Spectrom 2017;3:1–6. doi:10.1016/j.clinms.2017.02.001